Quantification of Caffeine in Energy and Cola Drinks via Rapid High Performance Liquid Chromatography Assays with Ultra Violet Diode Array Detection - Christopher E. Karlsen; Jake A. Cravino; Arianne Soliven; Peter J. Mahon; Feng Li; R. Andrew Shalliker (Beverages)
There is currently a lack of regulation of the caffeine found in cola and energy drinks by the FDA, which fails to protect the consumers of these products. Due to this lack of regulation, cola and energy drinks can have noticeable differences in their caffeine content when compared to the average amount per serving labelled on the product. In this study, we demonstrate the ability to analyse caffeine rapidly in under 20 s, and with HPLC pressures under 3500 psi (241 bar). To facilitate a high-throughput routine HPLC analysis of the caffeine content found in energy and cola drinks, two HPLC column technologies are studied, a conventional run HPLC column, and a newly commercialised Radial Flow Splitting end fitted HPLC column. The Radial Flow Splitting fitted column demonstrated the following benefits: a 37% reduction in pressure, an increased signal intensity sensitivity of 35%, a reduced analysis time by 20%, and improved metrics in assay precision based on triplicate injections associated with retention time, peak area, and peak height precision %RSD values. Both rapid HPLC methods offer greater opportunity for expanded beverage testing, which can ultimately help protect the consumer. The quantified energy drinks that were tested had a higher caffeine content, on average, than the labelled caffeine content, with an approximately ±16 mg difference per serving size for the energy drinks. In the case of the cola drinks, which did not include caffeine levels on the food label, we compared the levels to the USDA guidance and found up to double the recommended amount of caffeine in one serving for the samples studied. This highlights the need to have stricter regulations for caffeinated beverages to protect consumers and provide transparency regarding the caffeine content.